Forces of change new strategies for the evolving health care marketplace - Shore, David A. (J-b public health/health services text, 2012)
"This groundbreaking book is based on an innovative model developed by David Shore that serves as the foundation for his Forces of Change program. Forces of Change offers an invaluable guide and sourcebook for the latest thinking on how organizations and their leaders can navigate an ever-changing health care marketplace. The book's emphasis on creating competitive advantage and developing implementation strategies could scarcely be more timely or more in demand"--